Utilization of Cempedak (Artocarpus champeden) by Communities in Sabun Village, Central Aitinyo Sub-district, Maybrat Regency, West Papua Province - Ariance Juli Ross Nauw; Sepus M Fatem; Susilo Budi Husodo; Mecky Sagrim (Jurnal Ilmu Kehutanan)
Cempedak (Artocarpus champeden) is one of the non timber forest products (NTFPs) from the Maybrat district. It is used as a daily food of Maybrat people. The study was conducted from June-July 2014 in Sabun Village, Aitinyo Sub district of the Maybrat Regency, West Papua Province. The objectives of this study were to explore the utilization, harvesting technique, and manufacturing process of cempedak in Sabun villages. Field observations and interviews were used to collect the data of 15 respondents. The result showed that fruits and seeds are part of of the cempedak trees, which is utilised for food. Cempedak processing were divided into 3 parts i.e. the ripe fruit, the unripe fruit, and the seed. Processing of the seed were divided into four parts i.e. boiling, steaming, frying without oil process, filling inside bamboo, and storage. Conservation efforts were conducted by planting cempedak in the garden of villagers’ house. This research also revealed that the utilization process was done for household purposes only. Therefore, the development of cempedak for an alternative food as NTFPs, is necessary to be promoted by collaboration of related stakeholders including forestry and agriculture in Maybrat Regency.